Against the World: Joel's External Conflict in The Last of Us Season 1 - I Gusti Ngurah Gilang Parayudha; I Wayan Juniartha (Universitas Islam Negeri Palopo, 2025)
This research explores the types of external conflicts and conflict management strategies used by the main character, Joel, in The Last of Us Season 1. Using a qualitative descriptive method, the research analyzes all nine episodes by observing, identifying, and classifying Joel’s external conflicts based on Kenney (1966) theory man vs. man, man vs. nature, and man vs. society. It also applies the conflict management strategies from Thomas & Kilmann (2012): competing, avoiding, collaborating, accommodating, and compromising. The findings reveal 17 external conflicts, with man vs. man and man vs. nature each accounting for 35%, and man vs. society 30%. In responding to these conflicts, Joel mostly uses the competing strategy (53%) and avoiding strategy (47%). Competing is seen when he takes direct, forceful action, while avoiding appears in situations that are emotionally overwhelming or where he lacks control. This research is significant for media and literary studies because it shows how conflict in a post-apocalyptic narrative shapes character development and reflects human survival instincts. By focusing on one character across a full season, the research offers a detailed look at how external pressures influence behavior and decision-making in extreme conditions. However, the scope is limited to Joel and does not cover internal conflict or perspectives from other characters. Future studies are encouraged to explore more characters, compare seasons, or examine similar themes in different genres to gain broader insights.